2020
DOI: 10.3390/molecules25143163
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid Extraction of Celery and Parsley Fruit-Chemical Composition and Antibacterial Activity

Abstract: Supercritical fluid extraction as an environmentally friendly technology was applied to isolate biologically active extracts from celery and parsley fruits for potential applications in the food industry. The extractions were performed under mild temperature conditions of 39.85 °C and at pressures of 10 and 30 MPa. The extracts were analyzed regarding their chemical composition, antibacterial activity, and cytotoxic effect. Sedanolide was the dominant component of the celery fruit extracts, comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Overall, the growth of pathogens in carrot and celery was controlled better than in cabbage and paprika at 5 and 15 °C. Antimicrobial activities of water-soluble polysaccharides in carrot and sedanolide (aroma component) in celery might explain such results [ 51 , 52 ]. Consequently, it can be concluded that combined treatment may extend the shelf life of fresh-cut vegetables, although the microbial reduction effect may vary depending on the characteristics of vegetables.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the growth of pathogens in carrot and celery was controlled better than in cabbage and paprika at 5 and 15 °C. Antimicrobial activities of water-soluble polysaccharides in carrot and sedanolide (aroma component) in celery might explain such results [ 51 , 52 ]. Consequently, it can be concluded that combined treatment may extend the shelf life of fresh-cut vegetables, although the microbial reduction effect may vary depending on the characteristics of vegetables.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of phenolic compounds in the parts of Apium graveolens L. is the reason why celery is the plant most used in traditional medicine [180,181]. Previously published photochemical studies have shown that extracts of Apium graveolens L. are rich in bioactive compounds such as polyphenols and flavonoids [182,183] (Figure 8). It is well known that these secondary compounds present in Apium graveolens L. have considerable pharmacological activities, suggesting that the activities mentioned below may be due to these secondary metabolites.…”
Section: Grape Seeds Aqueous Extract Micementioning
confidence: 99%
“…One of the most common approaches for packaging films with improved antimicrobial properties is based on the release of active compounds from the packaging material into the close surroundings [ 3 ]. Due to stricter standards nowadays in the food industry and the ban on the usage of many substances that were previously allowed in food production [ 4 ], natural biodegradable polymers have the advantage of being used for active packaging in comparison to synthetic materials. For the same reasons, instead of synthetic chemicals, mostly molecules of natural origin are preferred to deliver the activity to the food packaging material.…”
Section: Introductionmentioning
confidence: 99%